Sympathetic nervous system inhibition enhances cardiac metabolism and improves hemodynamics and glucose-insulin dynamics in obese and lean rat models - Ionuț Tudorancea; Ionela Lăcrămioara Șerban; Dragomir N. Șerban; Irina-Iuliana Costache-Enache; Caratașu Cătălin; Alexandru Grațian Naum; Radu Iliescu (Scientific Reports)
Abstract This study aimed to investigate the effects of chronic sympathoinhibition on glucose uptake by the myocardium and by the skeletal muscle in an animal model of obesity associated with leptin signaling deficiency. 6 obese Zucker rats (OZR) and 6 control Lean Zucker rats (LZR) were studied during basal conditions, chronic clonidine administration (30 days, 300 µg/kg), and washout recovery period. Glucose uptake in the myocardium and in the skeletal muscle was measured using positron emission tomography (PET) and 2-[18F] fluoro-2-deoxy-D-glucose ([18F]FDG). The standardized uptake value (SUV) corrected for blood glucose was used for the semi-quantitative analysis. Body weight, food and water intake, blood glucose concentration, blood pressure variability as an index of sympathetic activity and hemodynamic parameters such as mean arterial blood pressure (MAP), systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were analyzed. Myocardial glucose uptake was significantly lower during basal conditions in OZR versus LZR. In both OZR and LZR, chronic clonidine significantly reduced myocardial glucose uptake and hemodynamic variables (such as MAP, SBP, DBP, HR), and sympathetic activity (SA). [18F]FDG skeletal muscle uptake did not significantly differ in OZR versus LZR. Our findings indicate that cardiac glucose metabolism is reduced in obesity presumably in relation with the level of sympathetic activation.